Blue Ocean Strategies for E.ON to strengthen the customer base in the Public Sector - Paramashivaiah, Roshan (2009)
In UK the energy distribution companies are popular for the price wars and differentiation in their offerings. The main objective of this report is to provide feasible blue ocean strategies for E.ON in the public sector mainly for the higher education universities and NHS hospitals. This report starts with the in-depth analysis of E.ON business. Then the value chain of the E.ON is understood after which some of the key stakeholders in the public sector has been identified. It is followed by a wider scan of the environment through PEST which takes into consideration the risks and challenges in the industry. Then the focus is shifted to the current and future strategies of the competitors and their areas of interest. Then the report concludes with the analysis of the energy services business of E.ON. In this section a complete analysis of the current situation, opportunities, evolving technologies in energy services have been identified. It is followed by a financial analysis, which provides complete details of the investment required and payback period for the energy services offering to the higher education universities and NHS hospitals in UK. The report ends with the information on some of the risks and opportunities for E.ON in public sector.